EFFECT OF PRODIGIOSIN FROM SERRATIA MARCESCENS BR1 STRAIN AS AN ANTIOXIDATIVE, ANTIMICROBIAL, AND IN VIVO WOUND HEALING - HACENE, ELHAMEUR (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The aim of this work is to evaluate antioxidative, antimicrobial, and healing wound potential of prodigiosin extracted from Serratia marcescens strain microbiota of a traditional Algerian fermented cereal food. The goal is to develop a natural galenic formulation for external use. Methods: After extraction and purification of the red pigment, the Fourier transform infrared spectrum is determined. The antioxidative activity was performed by scavenging radical with 2-diphenyl-1-picrylhydrazyl (DPPH), bleaching of beta-carotene, and ferric reducing antioxidant power. Antimicrobial tests were assessed against bacteria and fungi pathogenic reference strains Escherichia coli ATCC 25922, Enterococcus faecalis ATCC 10541, Klebsiella oxytoca ATCC 13182, Staphylococcus aureus CC 10541, Helicobacter pylori, and Candida albicans ATCC 10231. Healing wound activity was achieved in vivo on Wistar rats using as a reference to the commercial formulation Madécasol. Results: S. marcescens BR1 produce a prodigiosin where IR spectrum is typical. The DPPH test shows a trapping power of 80% at 1 mg/ml and an inhibitory concentration 50 equal to 0.54 mg/ml. The discoloration of β-carotene is 50% with high ferric reducing antioxidant power (FRAP). Candida albicans were the most sensitive to prodigiosin with inhibition diameters >20 mm. All strains tested are sensitive to prodigiosin. C. albicans were the most sensitive with inhibition diameters >20 mm followed by H. pylori strain (15 mm) and E. coli (13.5 mm). Prodigiosin ointment at 0.1% in Vaseline was used to achieve in vivo healing activity. Obtained results showed a fast and effective wound healing potential, better than the standard (Madécasol). The cicatrization traces totally without any of the lesions. We discovered the absence of the redness phase. This formulation, based on prodigiosin, is very promising as a natural replacement for the synthetic drug, having powerful anti-microbial, wound healing, and anti-inflammatory activities.